2016
DOI: 10.1037/pag0000134
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive activity mediates the association between social activity and cognitive performance: A longitudinal study.

Abstract: Social activity is one aspect of an active lifestyle and some evidence indicates it is related to preserved cognitive function in older adulthood. However, the potential mechanisms underlying this association remain unclear. We investigate four potential mediational pathways through which social activity may relate to cognitive performance. A multilevel structural equation modeling approach to mediation was used to investigate whether cognitive activity, physical activity, depressive symptoms, and vascular hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 80 publications
4
39
0
Order By: Relevance
“…Older adults’ social domains may have a positive impact on their cognitive function. Previous studies have indicated that poor social relationships, low levels of social activity and low social engagement are associated, not only with cognitive decline [ 38 , 39 ], but also with an increased risk of dementia [ 40 , 41 , 42 ]. As several issues in each domain, including the definition of frailty, need to be further explored, future studies should analyze the relationships between the various domains, including cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults’ social domains may have a positive impact on their cognitive function. Previous studies have indicated that poor social relationships, low levels of social activity and low social engagement are associated, not only with cognitive decline [ 38 , 39 ], but also with an increased risk of dementia [ 40 , 41 , 42 ]. As several issues in each domain, including the definition of frailty, need to be further explored, future studies should analyze the relationships between the various domains, including cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…by focusing on physical health or social engagement, but rarely both). Previous studies which have assessed various aspects of lifestyle have tended to rely on separate linear regressions (6)(7)(8), mediation analyses (9) or sum scores (10,11) for their analyses, limiting the extent to which possible complementary benefits of lifestyle can be detected. Thus, unless these factors are analysed conceptually and mathematically simultaneously, it remains an open question as to whether individual lifestyle factors will 'sum up' to demonstrate incremental benefits, or rather be redundantly associated with better outcomes (see also Kremen et al, 2019 (12)).…”
Section: Lifestyle and Healthy Ageingmentioning
confidence: 99%
“…Aging is broadly associated with progressive impairment in hippocampal function in mammals (Bettio et al, 2017 ). Both cross-sectional and longitudinal studies suggest that humans with more social ties have better preservation of cognitive function, particularly hippocampal-dependent forms of memory, in old age than those with fewer ties (Bassuk et al, 1999 ; Seeman et al, 2001 ; Béland et al, 2005 ; Ertel et al, 2008 ; Haslam et al, 2015 ; Brown et al, 2016 ). Causation, however, has been difficult to determine in humans and clinical trials of social network interventions have yielded unclear results (Hogan et al, 2002 ; Green et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%